ANALISIS PENERAPAN STANDAR SARANA PRASARANA DI SDN BEJI 01 KECAMATAN UNGARAN TIMUR - Tutik Yuliarsih; Dyah Ayu Permatasari; Farid Ubaidillah; Sudjono, Sudjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Educational facilities and infrastructure are very important components in supporting the optimal implementation of the educational process. According to Barnawi, educational facilities and infrastructure are "all basic equipment that indirectly supports the implementation of the educational process in schools. "Therefore, educational facilities and infrastructure are a unit that supports the implementation of the learning and teaching process well and optimally." The problem to be studied focuses on the availability and management of facilities and infrastructure at SD Negeri Beji 01, East Ungaran District. The aim that is expected to be achieved in this research is to find out how the availability and management of facilities and infrastructure is at SD Negeri Beji 01, East Ungaran District. In this research, the author used qualitative research methods. The research method uses qualitative methods and a descriptive approach. Based on the results of field research and data analysis that the author has carried out, it can be concluded that the condition of the facilities and infrastructure at SD Negeri Beji 01 can be categorized as adequate but require maximum maintenance and optimal use.